Pemberdayaan Masyarakat Melalui Penyuluhan Perawatan Gigi Dan Mulut Pada Anak Sekolah TK Kabar Baik di Desa Ajibaho Kabupaten Deli Serdang Tahun 2022 - Arva Rochmawati; Desi Anggraini (Indonesian Journal Publisher, 2022)
Cavities are still a common complaint in both children and adults. This condition cannot be ignored as it can affect a person's quality of life by causing pain, discomfort, disability, acute and chronic infections, eating and sleeping disorders, as well as a high risk of hospitalization. As a result, medical costs can increase significantly. One of the main causes of oral health problems in children is the lack of knowledge about how to maintain oral health. To address this issue, a health counseling was conducted focusing on